Kandungan Gizi dan Karakterisasi Senyawa Bioaktif Lintah Laut (Discodoris sp.) [Nutritional Content and Characterization Bioactive Compounds of Sea Sluge (Discodoris sp.) ] - Hafiluddin Hafiluddin; Nurjanah Nurjanah; Tati Nurhayati (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract One of the commodities produced from the ocean that have a bioactive compounds is a sea slug (Discodoris sp.). That is very interesting to study mainly deals with the nature of both chemical and biochemical characteristics and their use for the field of food and health. The aims of this research was to determine the nutrient content of sea slug, determaine chemical content and determine antioxidant activity. The experiment was conducted with several stages: sample preparation, analysis of nutrient content, extraction bioactive compound, analysis of chemical content and antioxidant activity.  Sea slug from the island of Madura Pamekasan potential as a source of protein, fat, and minerals. Sea slug has esensial amino acids amount to 5.57% was dominated by leucin of 1.42%. Nonesensial amino acids amount to 6.54% wich was dominated by glutamic acid 2.19%.  Saturated fatty acids amounted to 27.53% of sea slug was dominated by palmitic (C16: 0) which was 13.36%. Unsaturated fatty acids amounted to 34.66%, which was dominated by the essential fatty acids linolenic (C18: 3, n-3) 20.91%. The highest yield of the crude extract was ethanol and contained alkaloid compounds, steroids, phenols, carbohydrates and reducing sugar compound. The meat of sea slug with ethanol solvent has an IC best 50 antioxidant activity at 441, 12 ppm.